20 What happens to platelet function and vascular inflammation when clopidogrel is withdrawn? Insights using short thrombelastography. (9th June 2011) - Sambu, N; Dent, H; Warner, T; Englyst, N; Leadbeater, P; Hobson, A; Calver, A; Corbett, S; Gray, H; Simpson, I; Curzen, N
Abstract : Introduction: A clustering of adverse events, in particular stent thrombosis (ST) has been observed following clopidogrel cessation 1-year after drug-eluting stenting (DES), the aetiology of which is poorly understood. We investigated the effect of withdrawing clopidogrel in DES patients using a simple, rapid, reproducible near-patient platelet function test known as short Thrombelastography (s-TEG) that has been developed and validated by this group. Methods: 33 patients on aspirin and due to stop clopidogrel at 1 year following DES were investigated. Venesection was performed at (i) 4 weeks and 24 h pre clopidogrel cessation (ii) 24 h, 48 h, 1, 2 and 4 weeks post clopidogrel cessation. At all time-points, platelet reactivity was determined using s-TEG and thromboxane (TX) B2, IL-6, CD40 ligand and high sensitivity CRP were measured. Results: Clopidogrel cessation produced (i) a predictable increase in ADP-induced platelet aggregation, and (ii) an unexpected and significant rise in AA-induced platelet aggregation. TXB2 was consistently suppressed confirming inhibition of COX by aspirin. Conclusion: We have described for the first time an aspirin-independent increase in AA-induced clotting following clopidogrel withdrawal in DES patients. As well as potentially helping to explain the observed clustering of ST events early after clopidogrel withdrawal, these findings raise the question as to whether AA-induced clotting is an appropriate test of aspirin sensitivity. Our results also confirm s-TEG as a plausible candidate for near-patient platelet function testing in this field.